Problems of Development of the Venture Capital Industry in the Republic of Armenia - Arshakyan, Kristine (Bulletin of Yerevan University G: Economics, 2023)
The venture capital industry is crucial for the development of start-up companies, their entry into the international market and rapid growth, as well as for the development of the country’s economy. In Armenia, the venture capital industry is still under development and despite some progress within the industry, there are serious challenges such as the low attractiveness of the country for investments, low reputation of Armenian start-up companies among international venture investors, less funding opportunities, insufficient state support for the development of the industry and other challenges. Armenian start-up companies often try to attract investments from foreign venture funds, though they rarely succeed due to insufficient reputation among these funds, and if they succeed, they have to register the start-up company in the country of the investor, to secure the investments from a legal point of view. For the purpose of identifying these and other problems in the venture capital industry of Armenia, this paper examines the current state of the industry, the attractiveness of the investment environment in Armenia, the advantages and disadvantages of the legislative framework, international experience in the development of the venture capital industry, as well as the importance of state support. Revealing the problems will make it possible to develop corresponding recommendations that will contribute to the development of the venture capital industry in Armenia.
Keywords: venture capital; venture capital investments; startup companies; startup ecosystem; attractiveness of investment environment; venture capital fund; investment transaction